2008
DOI: 10.1158/0008-5472.can-07-3212
|View full text |Cite
|
Sign up to set email alerts
|

Induction of EBV–Latent Membrane Protein 1–Specific MHC Class II–Restricted T-Cell Responses against Natural Killer Lymphoma Cells

Abstract: EBV-encoded latent membrane protein 1 (LMP1) has oncogenic potential and is expressed in many EBV-associated malignancies. Although LMP1 is regarded as a potential tumor-associated antigen for immunotherapy and several LMP1-specific MHC class I-restricted CTL epitopes have been reported, little is known regarding MHC class II-restricted CD4 helper T-lymphocyte (HTL) epitopes for LMP1. The goal of the present studies was to determine whether MHC class IIrestricted CD4 T-cell responses could be induced against t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
1
26
1
1
Order By: Relevance
“…Our results showed that these malignant T and NK cells had the machinery for antigen-processing and presentation, were recognized by polyclonal effectors containing LMP2-specific CTLs as minor populations, and more importantly, by LMP2-specific CD8 ϩ clones; efficiently recognizing multiple LMP2 epitopes across 3 different restriction elements. These data greatly strengthen the isolated reports describing killing of T and NK lines by EBNA1 41 or LMP1 42,43 clones by extending to the most immunogenic and clinically relevant of available targets, LMP2. Our data provide a rationale to pursue adoptive CTL immunotherapy for patients with ENKTL and CAEBV.…”
Section: Discussionsupporting
confidence: 82%
“…Our results showed that these malignant T and NK cells had the machinery for antigen-processing and presentation, were recognized by polyclonal effectors containing LMP2-specific CTLs as minor populations, and more importantly, by LMP2-specific CD8 ϩ clones; efficiently recognizing multiple LMP2 epitopes across 3 different restriction elements. These data greatly strengthen the isolated reports describing killing of T and NK lines by EBNA1 41 or LMP1 42,43 clones by extending to the most immunogenic and clinically relevant of available targets, LMP2. Our data provide a rationale to pursue adoptive CTL immunotherapy for patients with ENKTL and CAEBV.…”
Section: Discussionsupporting
confidence: 82%
“…The attention has been focused on cytotoxic CD4 + T cells, which proved to be effective, at least in vitro, not only against EBV LCL but also, more importantly, against infected NK or T cells, the natural target in NK/Tcell lymphoma and CAEBV. 86,87 Such observations differ from the previous reports related to these diseases [82][83][84][85] which only demonstrated the activity against LCL that express a larger pattern of viral antigen and costimulatory molecules than EBV-infected NK/T cells.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 85%
“…Although LMP1 may render the cell malignant phenotype, these alterations should be involved in host immune response and may affect the manner of tumor progression. Previous in vitro studies show that cytotoxic T cells against LMP1 can directly kill ENKLderived cell lines (35,36). Therefore, LMP1 may have reciprocal effects on the expressing cells, that is, even though LMP1-expressing cells show a malignant phenotype, an extrinsic immune system can eradicate these cells in vivo.…”
Section: Discussionmentioning
confidence: 99%